Structural change revisited: The rise of manufacturing jobs in the service sector - Dominik Boddin; Thilo Kroeger (Deutsche Bundesbank, 2021)
This paper reconsiders the labor market consequences of structural change over the past 43 years. Taking two different ways of defining manufacturing and service employment as point of departure - according to the industry classification of firms or establishments and according to the occupation and hence the tasks of the workers - we show that structural change is far less pronounced than generally perceived. Manufacturing and service employment numbers based on the occupations of workers deviate markedly from the employment numbers based on the industry classification of employers. The decline in manufacturing jobs in Germany is far lower if the measurement of employment is based on the occupation of the worker. About 52% of manufacturing jobs that were lost in manufacturing industries between 1975 and 2017 are offset by new manufacturing jobs in service industries. This also has important implications for empirical applications. By way of example, we reestimate the effect of international trade on manufacturing employment based on the occupation of the worker. Contrary to previously identified negative effects, we cannot identify significant effects of import exposure on employment in manufacturing occupations. Using detailed, comprehensive German social security data, we show at the worker level that the service sector increasingly acts as a valuable alternative employment option for workers with manufacturing occupations. We estimate the causal effects of a switch to the service sector on employment outcomes by following workers over time after mass layoffs. The results reinforce our claim that structural change is less pronounced than perceived, as workers who retain their initial occupation and switch to employment in the service sector experience no significant differences in future employment trajectories compared to workers who manage to stay in the manufacturing sector.
Keywords: J21; J24; L23; E24; D22; F61; 330; Employment Structure; Structural Change; Organization of Production; Occupations; Within-Firm Adjustments; Germany